Genome-wide analysis of peptidase content and expression in a virulent and attenuated Babesia bovis strain pair - Mesplet, Maria (2011)
Identifying virulence determinants in Apicomplexan parasites remains a major gap in knowledge for members within this phylum. We hypothesized that peptidases would segregate with virulence between a virulent parent Babesia bovis strain and an attenuated daughter strain derived by rapid in vivo passage. Using the complete genome sequence of the virulent T2Bo strain, 66 peptidases were identified and active sites confirmed. The presence, sequence identity and expression levels were tested for each of the 66 peptidases in the virulent parent and attenuated daughter T2Bo strains using whole genome, targeted sequencing approaches and microarrays analyses. Quantitative PCR revealed that there was no significant difference in peptidase expression between the virulent and attenuated strains. We conclude that while peptidases may well play a required role in B. bovis pathogenesis, neither loss of peptidase gene content nor reduced gene expression underlies the loss of virulence associated with in vivo passage and attenuation.